Analysis of Slang as a Linguistic Mechanism in Verbal Bullying among Elementary School Students - Putri, Winda Purnama; Wulandari, Murfiah Dewi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study examines the transformation of slang from an expressive form of language into a linguistic mechanism of verbal bullying among elementary school students. A qualitative case study was conducted at Nanggungan Elementary School involving the principal, teachers, and sixth-grade students. Data were collected through semi-structured interviews, classroom observations, and documentation, and were analyzed using the Miles and Huberman interactive model. The findings reveal that slang primarily targets physical appearance and intellectual ability, with digital media emerging as the dominant source, followed by peer interaction and, to a lesser extent, family influence. The use of derogatory slang contributes to decreased learning motivation, reduced self-confidence, emotional distress, and weakened peer relationships. This study underscores the urgent need to strengthen language ethics education, character development programs, and digital literacy initiatives in primary schools to prevent the normalization of slang-based verbal bullying and to foster a respectful and inclusive communication environment.